2,6-[Bis(dimethylamino)methyl]phenylselenenyl chloride/bromide monohydrate - Anand Gupta (IUCrData, 2017)
In the title hydrated salt, C12H19N2Se+·Cl0.44/Br0.56−·H2O, the halide ions (both with site symmetry 2) have different Cl−/Br− occupancies of 0.399 (2)/0.601 (2) and 0.491 (2)/0.509 (2). In the crystal, the cation and anion are linked by an Se...X (X = Cl/Br) interaction of length 3.5593 (8) Å. The water molecule and anions are linked by O—H...X hydrogen bonds into a staggered chain propagating in the b-axis direction and the packing is consolidated by weak C—H...X interactions.